A longitudinal study on associations of moderate-to-vigorous physical activity with plasma monounsaturated fatty acids in pregnancy - Xia, Tong; Chen, Liwei; Fei, Zhe; Liu, Xinyue; Dai, Jin; Hinkle, Stefanie N.; Zhu, Yeyi; Wu, Jing; Weir, Natalie L.; Tsai, Michael Y.; Zhang, Cuilin (Frontiers in Nutrition, 2022)
Background: Physical activity (PA) during pregnancy influences women and offspring’s health via fatty acids metabolism. However, studies on associations of PA with plasma monounsaturated fatty acids (MUFAs) across pregnancy are sparse. Thus, our study aimed to examine associations of PA with individual plasma phospholipid MUFAs throughout pregnancy in a prospective and longitudinal study in the United States. Methods: The study included 318 pregnant women from the Eunice Kennedy Shriver National Institute of Child Health and Human Development Fetal Growth Studies-Singletons cohort. PA was measured four times: PA reported at 10–14 gestational weeks (GWs) representing PA in past year, and at 15–26 GWs, 23–31 GWs, and 33–39 GWs representing PA since the last visit. Plasma phospholipid MUFAs were measured at the same four visits as measurement of PA. Associations between moderate-to-vigorous PA (MVPA) and the total MUFAs and 7 individual plasma phospholipid MUFAs (i.e., palmitoleic acid, 18:1n6-9 trans, 18:1n6c, cis-vaccenic acid, oleic acid, eicosenoic acid, and nervonic acid) were assessed at each visit using multivariable linear regression models adjusting for confounders. Results: MVPA (hours/week) reported at 15–26 GWs representing MVPA since the last visit was positively associated with total MUFAs (% of total fatty acids) [adjusted β*102 (standard error (SE)*102) = 10.41 (3.19), P = 0.001] at 15–26 GWs. For individual MUFAs, MVPA reported at 15–26 GWs representing MVPA since the last visit was positively associated with oleic acid [adjusted β*102 (SE*102) = 8.56 (2.65), P = 0.001] and eicosenoic acid [adjusted β*102 (SE*102) = 0.55 (0.20), P = 0.01] at 15–26 GWs. MVPA reported at 23–31 GWs representing MVPA since the last visit was positively associated with palmitoleic acid [adjusted β*102 (SE*102) = 2.24 (0.64), P = 0.001] at 23–31 GWs. MVPA reported at 10–14 GWs and 33–39 GWs was not associated with total or individual MUFAs. Conclusions: We found novel positive associations of MVPA with individual MUFAs such as oleic acid, eicosenoic acid, and palmitoleic acid during the middle-to-late pregnancy. These findings suggest that MVPA represents a potential modifiable factor for plasma individual MUFA levels during pregnancy.